Tanggung Jawab Perusahaan Multinasional dalam Kebakaran Hutan di Indonesia - Gintoe, Chris Sostom (University of Merdeka Malang, 2019)
Indonesia as a country that exports smoke also causes losses in neighboring countries and the impact of the haze has an impact on the economy, tourism and health in surrounding countries. Based on this, in this paper describes the problem identification as follows first, what is the position of multinational companies according to the Republic of Indonesia Law Number 40 of 2007 concerning Limited Liability Companies. Second, what is the form of responsibility of multinational companies in terms of forest fires in Indonesia in the perspective of international environmental law. The method used in this study is a normative juridical method that is descriptive. The case of forest fires in Indonesia carried out by multinational companies can be burdened with responsibility in accordance with the conditions in which the company operates. This is because the internal law of Bleum is able to directly impose legal responsibility on corporations and state authority is still needed to sanction the law as an intermediary. International law has still not moved from the use of the classical negocentric theory. Criminal and administrative provisions can be used in prosecuting a corporation.How to cite item:Â Gintoe, C. (2019). Tanggung Jawab Perusahaan Multinasional dalam Kebakaran Hutan di Indonesia.Â Jurnal Cakrawala Hukum, 10(1), 30-39. doi:https://doi.org/10.26905/idjch.v10i1.2808